EKSISTENSI PARALEGAL DALAM PENINGKATKAN KUALITAS LAYANAN BANTUAN HUKUM DITINJAU DALAM PUTUSAN MAHKAMAH AGUNG NOMOR 22 P/HUM/2018 - Nurpian, Masan (E-Journal Widya Yustisia, 2020)
The role of paralegals can be said to be the spearhead as well as a catalyst for conflict handling in a community, community, rural area, or certain areas. Paralegals at the community level act as a liaison between the community and legal aid organizations to provide legal assistance. Supreme Court Decision Number 22 P / HUM / 2018 concerning Material Review of Minister of Law and Human Rights Regulation Number 1 of 2018 concerning Paralegals in Providing Legal Aid which annulls the role of litigation and non-litigation by Paralegals This research aims to examine the existence of paralegals in improving the quality of assistance services law both outside and inside the court and to study the existence of paralegals in providing legal assistance in the judicial system in Indonesia, it is reviewed based on the decision of the Supreme Court Number 22 P / HUM / 2018. The research method used focuses on library data research, so the steps in this study use juridical logic. A normative approach to law identifies and conceptualizes law as norms, rules, regulations, legislation, which applies at a certain time and place as a product of the sovereign State. It can be concluded that the distribution of Advocate practices is not evenly distributed in every Regency / City, especially in rural areas, is still very minimal, therefore Paralegals who have been born from certain communities and societies need to be optimized and their existence considered. It is also hoped that paralegals will become the main actors in solving legal problems through alternative channels or without always having to go to court.